Pemanfaatan Limbah Tempurung Kelapa Menjadi Briket sebagai Upaya Mitigasi Perubahan Iklim pada Masyarakat Pesisir Distrik Bonggo, Kabupaten Sarmi - Elisabeth V. Wambrauw; Rosye H.R. Tanjung; Agustinus Agustinus; Anastasia S. Werdhani; Monita Y. Beatrick; Leonard Siregar; Allan B. La Andy (JURNAL PENGABDIAN PAPUA, 2026)
Coastal communities are increasingly vulnerable to climate change impacts, highlighting the importance of strengthening local adaptive capacity through sustainable resource utilization. This community service program aimed to improve community knowledge and skills in converting coconut shell waste into environmentally friendly briquettes as an alternative energy source in Armopa, Tarontha, and Narum Villages, Bonggo District, Sarmi Regency, Papua. The program applied a participatory approach involving resource assessment, community coordination, briquette production training, monitoring, evaluation, and the provision of charcoal grinding machines. The training was conducted on 6–8 September 2024 and involved 79 participants from the three villages. The results showed that participants were able to perform all stages of briquette production, including carbonization, charcoal crushing, binder mixing, molding, and drying. The program enhanced community capacity to utilize coconut shell waste as a renewable energy source, reducing dependence on firewood and kerosene. In addition to environmental benefits through biomass waste utilization, coconut shell briquettes offer economic opportunities to support local livelihoods. Program sustainability is supported by abundant raw materials, village government support, and appropriate technology assistance, although greater youth participation remains necessary for future development.